2018
DOI: 10.4103/phrev.phrev_46_17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mucuna pruriens (L.) supplementation on experimental models of parkinson's disease: A systematic review

Abstract: Introduction:Mucuna pruriens (L.)DC. (Mp) has been used in the treatment of numerous diseases in Indian Ayurvedic medicine, mainly for delaying the symptoms of Parkinson's disease (PD), and has as its main component levodopa (L-DOPA). The aim of this work is to systematically review the effects of Mp supplementation on experimental models of PD due to its neuroprotective and antioxidant properties. MATERIALS AND Methods: The search was conducted through PubMed, ScienceDirect, Cochrane Library, and Scientific E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Additionally, the plant is used in the treatment of depressive neurosis and snakebites. Studies have shown the preventive effects of M. pruriens against neurological damage caused by bilateral carotid artery occlusion-induced global cerebral ischaemia in rats that warrants its adjuvant use to improve the life quality of PD patients [ 160 , 161 ].…”
Section: Role Of Natural Products In Nddsmentioning
confidence: 99%
“…Additionally, the plant is used in the treatment of depressive neurosis and snakebites. Studies have shown the preventive effects of M. pruriens against neurological damage caused by bilateral carotid artery occlusion-induced global cerebral ischaemia in rats that warrants its adjuvant use to improve the life quality of PD patients [ 160 , 161 ].…”
Section: Role Of Natural Products In Nddsmentioning
confidence: 99%
“…It can cross BBB as suggested by the presence of c-phycocyanin which is a product of spirulina, in the hippocampus. Also, it has shown cytoprotective activity against neurodegeneration via an antioxidant mechanism [ 38 , 39 , 43 - 45 ].…”
Section: Neuroprotective Effects Of Various Natural Productsmentioning
confidence: 99%
“…However, researchers focused on their commercial use and tend to formulate the drug delivery system of the formulations particularly the nano drug delivery systems for the bacterial algae. However, the use of marine algae as a commercial drug delivery system is limited because of its inability to cross BBB [ 45 - 49 ].…”
Section: Neuroprotective Effects Of Various Natural Productsmentioning
confidence: 99%